The Effect Of Asset Structure, Sales Growth, And Profitability On Capital Structure In Property And Real Estate Sub-Sector Companies Listed On The Indonesia Stock Exchange (2019-2023) - Irwanda, Resa; Kusuma, Indra Cahya; Melani, Maria Magdalena (Institut Bisnis dan Informatika Kesatuan, 2024)
This research aims to determine and analyze the influence of asset structure, sales growth and profitability on capital structure. The population in this research are property and real estate sub-sector companies listed on the Indonesian Stock Exchange (2019-2023). The sample for this research was 9 companies. The sampling technique used was purposive sampling. The data collection technique in this research uses documentation techniques in the form of company financial report data. Data were analyzed using descriptive statistics with multiple linear regression analysis by first testing variables from company characteristics. The results of this research show that asset structure, sales growth and profitability have a positive and significant influence on capital structure. Keywords: assets, profitability, sales, capital